IMF Applications of Purchasing Power Parity Estimates - Silver, Mick (IMF Working Papers; Working Paper ;, 2010)
The IMF's main uses of the International Comparison Program's (ICP) estimates of purchasing power parity (PPP)-adjusted Gross Domestic Product (GDP) are as an element of the formula used to help guide decisions on its members' quotas and in the World Economic Outlook (WEO). The paper outlines these uses and considers measurement issues particularly salient to IMF usage including: PPP imputations for member countries not participating in the ICP; PPP estimates for non-benchmark years; timeliness and periodicity of PPP estimates; economy groupings; and transparency. The paper was written as a chapter on ?IMF uses of PPPs? for the 2011 ICP Handbook.